Spreading dynamics of superposed liquid drops on a spinning disk - Sahoo, Subhadarshinee; Orpe, Ashish V.; Doshi, Pankaj (Physics of Fluids, 2018)
We have experimentally studied simultaneous spreading of superposed drops of two Newtonian liquids on top of a horizontal spinning disk using the flow visualization technique. An inner drop of high surface tension liquid is placed centrally on the disk followed by a drop of outer liquid (lower surface tension) placed exactly above that. The disk is then rotated at a desired speed for a range of volume ratios of two liquids. Such an arrangement of two superposed liquid drops does not affect the spreading behavior of the outer liquid but influences that of the inner liquid significantly. The drop spreads to a larger extent and breaks into more fingers (Nf) as compared to the case where the same liquid is spreading in the absence of outer liquid. The experimentally observed number of fingers is compared with the prediction using available theory for single liquid. It is found that the theory over-predicts the value of Nf for the inner liquid while it is covered by an outer liquid. We provide a theoretical justification for this observation using linear stability analysis. Our analysis demonstrates that for small but finite surface tension ratio of the two liquids, the presence of the outer interface reduces the value of the most unstable wave number which is equivalent to the decrease in the number of fingers observed experimentally. Finally, sustained rotation of the disk leads to the formation of droplets at the tip of the fingers traveling outwards. Published by AIP Publishing.